PEMBLOKIRAN DAN PERAMPASAN ASSET SEBAGAI INSTRUMEN PENEGAKAN HUKUM KORUPSI PERSPEKTIF MAQASHID SYARIAH: PEMBLOKIRAN DAN PERAMPASAN ASSET SEBAGAI INSTRUMEN PENEGAKAN HUKUM KORUPSI PERSPEKTIF MAQASHID SYARIAH - Mustaqim, Dede Al Mustaqim (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Corruption is an extraordinary crime that erodes the very foundations of national and state life. The freezing and seizure of corruptors' assets have become important instruments in the enforcement of anti-corruption law. This study aims to analyze the strategy of corruption law enforcement through asset freezing and seizure from the perspective of Maqashid Sharia. The research method used is normative legal research with a qualitative approach. Primary data were obtained from laws and government regulations, while secondary data were sourced from books, scientific journals, and articles. The results of the study show that asset freezing is a crucial step to prevent the spread and concealment of assets obtained from corruption. The main challenges in its implementation include the expertise of corruptors in hiding assets, the leniency of legal sanctions, and the lack of obligations to return illicit wealth. Asset forfeiture without conviction (Non-Conviction Based Asset Forfeiture or NCB) is recognized as a more effective method in addressing the limitations of conventional criminal asset forfeiture. NCB allows the seizure of assets without requiring a prior criminal conviction. From the perspective of Maqashid Sharia, asset freezing and seizure in corruption crimes emphasize the importance of justice, public interest (maslahah), and the protection of wealth. Freezing and seizing corrupt assets are considered in line with the principles of Maqashid Sharia because they can recover state losses, provide a deterrent effect to corruptors, and preserve societal welfare. Thus, this study concludes that asset freezing and seizure can serve as effective and legitimate instruments of corruption law enforcement from the Maqashid Sharia perspective. Their application must uphold the principles of justice, public benefit, and the protection of property.